Qualitative and Nutraceutical Characteristics after Storage of New Pear Selections in Emilia-Romagna Region - Giuseppina Caracciolo; Maria Luigia Maltoni; Giulia Faedi; Sandro Sirri; Gianluca Baruzzi (Agronomy, 2021)
The Emilia-Romagna region is excellent in European pear production. CREA Centro di Ricerca Olivicoltura, Frutticoltura e Agrumicoltura leads a breeding project co-founded by New Plant (a consortium of three growers’associations Apofruit, Apoconerpo, and Orogel Fresco) whose main objective is to improve fruit quality and nutraceutical parameters. The purpose of this study is to describe the qualitative characteristics of some new genotypes obtained by this breeding activity after cold storage, in comparison with the main cultivated varieties, ‘Abbé Fétel’, ‘William’s B.C’ and ‘Doyenne du Comice’. In 2013, 2014, and 2015, fruit samples, stored in a normal refrigeration room and after 100 dd, reaching the consumption ripening (2.5–3 kg/0.5 cm2), were analyzed to quantify the qualitative parameters: average weight, caliber, titratable acidity, soluble solids contents, skin color and overcolor, sugar and organic acids content, the antioxidant capacity, the total polyphenols, and ascorbic acid content. The results showed that the selection ‘CREA 171’, with red skin and yellow-cream flesh, outstood for the high antioxidant capacity due to the high content of polyphenols and ascorbic acid.